Non-Communicable Disease Morbidity Among Young Adults: A Cross-Sectional Study in Indonesia - Ika Puspita Asturiningtyas; Hadi Ashar; Sidiq Purwoko; Nissa Noor Annashr (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2023)
Noncommunicable Disease (NCD) has continued to pose a significant global burden, specifically regarding morbidity among young adults which has not been well studied. Therefore, this study aimed to assess the burden of NCD among young adults and identify correlating factors. It analyzed the 2018 Indonesian Basic Health Research, a nationwide study employing a cross-sectional design and linear systematic with Two Stage Sampling. The subject involved comprised 319,355 individuals in the 18-40 age group. Data were further analyzed using bivariate and multivariate analysis with logistic regression. The analysis results showed that 6% of young adults in Indonesia had one NCD or more. Young adults with higher Waist Circumference (WC) and higher Body Mass Index (BMI) had a higher risk of NCD (OR:1.58; 95%CI;1.52-1.65 and OR: 1.14; 95%CI:1.09-1.19, respectively). Furthermore, several sociodemographic factors exhibited significant correlation including older age, female sex, unemployment, higher educational and socioeconomic status, married and divorced, as well as living in an urban area (p-value<0.05). Unhealthy behavior such as consuming alcohol and smoking also increased the risk for NCD morbidity (OR:1.20; 95%CI;1.10-1.30 and OR: 1.19; 95%CI:1.10-1.27). Therefore, it was crucial to strengthen preventive programs targeting NCD among young adults by focusing on sociodemographic characteristics. This study also emphasized the importance of campaigns aimed at improving health behavior in this age group.